The Dynamic of Political Scandals in the Mediatized Lithuanian Public Sphere - Masiokaitė-Liubinienė, Austėja (Information & Media, 2018)
[full article and abstract in Lithuanian; abstract in English] The concept of mediatization, which analyzes how the dominance of media shapes political processes, is becoming continuously more relevant as a more important role is being assigned to the media in the public sphere. Despite the relevance, there are not many defined methods of analysis of political mediatization. This article presents such a method, which is designed for analyzing political scandals. This method adopts the concept of mediatization as a metatheory and uses the Veto Players theory to structure the political sphere and scandals in a way that allows for their analysis. A qualitative content analysis of three cases of Lithuanian political scandals, based on this method, is also presented. In the discussed cases, the interaction between the political and media actors appears to be very close and mutual. Not only do politicians take the initiative in asking for the political responsibility of the actors in the scandalous situations that the media reveal, but they also initiate the distribution of such information to the media, seeking the desired change of the status quo or the legitimization of their decisions. This provides means for talking about the self-mediatization of political actors.